A green perspective: Synthesis of 2-chloro-3-formylquinolines and its derivatives. Issue 2 (17th January 2021) - Patel, Ankitkumar J.; Dholakia, Amitkumar B.; Patel, Vishant C.
Abstract: This review summarizes the green synthetic methods and reactions of 2-chloroquinoline-3-carbaldehydes. The reactions are subdivided in groups on the basis of which type of method used, that is, microwave, ultrasound, and grinding/solvent free/water as solvent. Most reaction types have been successfully applied and used in the production of biological active compounds. Graphical Abstract: